Filamentous Hydrous Ferric Oxide Biosignatures in a Pipeline Carrying Acid Mine Drainage at Iron Mountain Mine, California. Issue 3 (16th March 2017) - Williams, Amy J.; Alpers, Charles N.; Sumner, Dawn Y.; Campbell, Kate M.
ABSTRACT: A pipeline carrying acidic mine effluent at Iron Mountain, CA, developed Fe(III)-rich precipitate caused by oxidation of Fe(II)aq . The native microbial community in the pipe included filamentous microbes. The pipe scale consisted of microbial filaments, and schwertmannite (ferric oxyhydroxysulfate, FOHS) mineral spheres and filaments. FOHS filaments contained central lumina with diameters similar to those of microbial filaments. FOHS filament geometry, the geochemical environment, and the presence of filamentous microbes suggest that FOHS filaments are mineralized microbial filaments. This formation of textural biosignatures provides the basis for a conceptual model for the development and preservation of biosignatures in other environments.